A STEADY-STATE APPROACH TO PREVENT VOLTAGE COLLAPSE IN POWER SYSTEM - Quirós Tortós, Jairo; Araya Padilla, Eddie (Ingeniería, 2013)
This paper presents a steady state approach to prevent voltage collapse in a power system. The power system operation close to stability boundaries is an important factor which may lead to voltage instability conditions. There are different ways to prevent voltage collapse in the power system; one of this is the correct coordination of the protection devices to avoid undesirable equipment disconnections.This paper proposes a new method to coordinate the back-up zone in the distance protection scheme. The methodology uses both Optimal Power Flow (OPF) and Continuation Power Flow (CPF) solutions to determine the impedance seen by the relay. These impedances are later compared to conclude which is the best option to set the parameter for the back-up zone in the relay. The methodology also considers the distance to Maximum Loading Point (MLP) and the corresponding Voltage Collapse Point (VCP). Therefore, undesirable disconnections can be avoided when the power system operates close to the stability boundaries. In order to demonstrate and validate the methodology, simulations are carried out on the IEEE 14-bus test system using MATLAB.